Using fun activities to improve listening skill - Hanna Andyani (Journal on English as a Foreign Language, 2015)
Based on the researcher’s experience in teaching English at MTsN Mojokerto, there are three problems dealing with the teaching of listening especially for the third year students: 1) most of the students’ scores on listening test are still under the minimum passing criterion (KKM), which is 60; 2 most students are not very enthusiastic in listening activities; 3) it is difficult for students to understand native speech in a tape recorder. Based on the problems, the main purpose of the study is to improve the ninth grade students’ listening skill using Fun Activity in the form of Games at MTsN Mojokerto. The design of this study was Classroom Action Research. The instruments were the listening tests, observation checklist and questionnaires. With the implementation of the games, the criteria of success were successfully achieved in Cycle 2. 74% of the total number of the students could get the scores more than 60 and 90% have positive responses on the implementation of games.